Cascading effects of climate extremes on vertebrate fauna through changes to low‐latitude tree flowering and fruiting phenology. (13th March 2015) - Butt, Nathalie; Seabrook, Leonie; Maron, Martine; Law, Bradley S.; Dawson, Terence P.; Syktus, Jozef; McAlpine, Clive A.
Abstract Forest vertebrate fauna provide critical services, such as pollination and seed dispersal, which underpin functional and resilient ecosystems. In turn, many of these fauna are dependent on the flowering phenology of the plant species of such ecosystems. The impact of changes in climate, including climate extremes, on the interaction between these fauna and flora has not been identified or elucidated, yet influences on flowering phenology are already evident. These changes are well documented in the mid to high latitudes. However, there is emerging evidence that the flowering phenology, nectar/pollen production, and fruit production of long‐lived trees in tropical and subtropical forests are also being impacted by changes in the frequency and severity of climate extremes. Here, we examine the implications of these changes for vertebrate fauna dependent on these resources. We review the literature to establish evidence for links between climate extremes and flowering phenology, elucidating the nature of relationships between different vertebrate taxa and flowering regimes. We combine this information with climate change projections to postulate about the likely impacts on nectar, pollen and fruit resource availability and the consequences for dependent vertebrate fauna. The most recent climate projections show that the frequency and intensity of climate extremes will increase during the 21st century. These changes are likely to significantly alter mass flowering and fruiting events in the tropics and subtropics, which are frequently cued by climate extremes, such as intensive rainfall events or rapid temperature shifts. We find that in these systems the abundance and duration of resource availability for vertebrate fauna is likely to fluctuate, and the time intervals between episodes of high resource availability to increase. The combined impact of these changes has the potential to result in cascading effects on ecosystems through changes in pollinator and seed dispersal ecology, and demands a focused research effort.